Neuronal Control of Bone Remodeling. (October 2017) - Corr, Alexander; Smith, James; Baldock, Paul
Although the brain is well established as a master regulator of homeostasis in peripheral tissues, central regulation of bone mass represents a novel and rapidly expanding field of study. This review examines the current understanding of central regulation of the skeleton, exploring several of the key pathways connecting brain to bone and their implications both in mice and the clinical setting. Our understanding of central bone regulation has largely progressed through examination of skeletal responses downstream of nutrient regulatory pathways in the hypothalamus. Mutations and modulation of these pathways, in cases such as leptin deficiency, induce marked bone phenotypes, which have provided vital insights into central bone regulation. These studies have identified several central neuropeptide pathways that stimulate well-defined changes in bone cell activity in response to changes in energy homeostasis. In addition, this work has highlighted the endocrine nature of the skeleton, revealing a complex cross talk that directly regulates other organ systems. Our laboratory has studied bone-active neuropeptide pathways and defined osteoblast-based actions that recapitulate central pathways linking bone, fat, and glucose homeostasis. Studies of neural control of bone have produced paradigm-shifting changes in our understanding of the skeleton and its relationship with the wider array of organ systems.